H HUBUNGAN KOMUNIKASI INTERPROFESIONAL DENGAN KOLABORASI PERAWAT-DOKTER DI IRNA RSUD H. DAMANHURI BARABAI - Noor Anna Murdiany (LPPM Universitas Sari Mulia, 2021)
Background: Interprofessional communication is an important skill that can improve the functioning of a high-quality team, in patient care by involving several disciplines such as doctors, nurses and other health teams. Collaboration is a form of collaboration between teams of health workers from different educational backgrounds to provide the best quality of service to patients and their families. Objective: To determine the relationship between interprofessional communication and nurse-doctor collaboration at IRNA RSUD H. Damanhuri Barabai. Method: The research design used cross sectional with total sampling technique. The research instrument used an interprofessional communication questionnaire and nurse-doctor collaboration that had been tested for validity and reliability. Data were analyzed using Chi Square test. Conclusion: There is a relationship between interprofessional communication with nurse-doctor collaboration at IRNA Hospital H. Damanhuri Barabai. Nurses and doctors are expected to improve their ability to communicate and collaborate in order to improve the quality of health services. It's a good thing to do.